2013
DOI: 10.1155/2013/401392
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Analysis of Transparency Conducting AZO Films by Using DC Power and RF Power Simultaneous Magnetron Sputtering

Abstract: DC power and RF power were introduced into the magnetic controlled sputtering system simultaneously to deposit AZO films in order to get an acceptable deposition rate with high quality transparency conducting thin film. The resistivity decreases with the RF power for the as-deposited samples. The resistivity of 6 × 10−4 Ω-cm and 3.5–4.5 × 10−4 Ω-cm is obtained for the as-deposited sample, and for all annealed samples, respectively. The transmittance of the AZO films with higher substrate temperature is general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…The optical transmittance of the optimized AZO film is only 3% lower at average from 400 to 700 nm when compared to commercial ITO. In addition, our film showed higher or same transmittance when compared to other AZO films found in the literature [46][47][48][49] with smaller thicknesses and/or subjected to heat treatments.…”
Section: Optical Properties Of the Azo Filmssupporting
confidence: 74%
“…The optical transmittance of the optimized AZO film is only 3% lower at average from 400 to 700 nm when compared to commercial ITO. In addition, our film showed higher or same transmittance when compared to other AZO films found in the literature [46][47][48][49] with smaller thicknesses and/or subjected to heat treatments.…”
Section: Optical Properties Of the Azo Filmssupporting
confidence: 74%
“…For example, cost effective solar cells based on Cu (In,Ga)Se 2 (CIGS) and Cu 2 ZnSnS 4 (CZTS) absorbers have been fabricated with a TCO based on AZO [6,7]. There are several methods used to deposit AZO, including physical vapor deposition (under various operation conditions for magnetron sputtering, such as radio-frequency [8][9][10][11][12][13][14][15][16][17][18][19][20], medium-frequency [8,[21][22][23][24][25][26], DC [8,16,22,[26][27][28][29][30][31][32][33][34][35][36][37], pulsed DC [38], high power impulse [39,40], ion beam assisted [41], chemical vapor deposition [1,5] and other chemical methods such as spin coating and sol gel [2,4]. Among them, magnetron plasma sputtering has been successfully used to deposit ITO on large area substrates (up to 15 m 2 ) and is also regarded as a viable and cost effective solution for AZO …”
Section: Introductionmentioning
confidence: 99%
“…Existing literature covers the impact of the fabrication method and deposition conditions [7,14,[18][19][20][21][22][23], the post-processing of the film (such as high temperature annealing treatments) [15,17,[24][25][26][27][28] or the role of the substrate in governing the properties of the TCOs [29,30]. In respect to the latter, most works use glass or SiO 2 as substrates [19,23,24,[31][32][33][34] or, more recently, flexible, lightweight materials like PET or PEN [30]. However, it is shown in these reports that the substrate plays a key role in the properties of the film and therefore it cannot be concluded that those films will have the same properties when grown on the actual substrate of interest.…”
Section: Introductionmentioning
confidence: 99%